Pengaruh Biaya Promosi terhadap Peningkatan Penjualan pada PT Lurus Jaya Mangngallei Kabupaten Gowa - Basir, Pegiawati; Sudirman, Sudirman; Idris, M. Abduh; Harun, Salmah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to determine and analyze the effect of promotional costs on sales growth at PT Lurus Jaya Mangngallei, Gowa Regency. The method used is a quantitative approach with a simple linear regression analysis technique. The data employed are primary data obtained from the company’s financial reports over the past three years. The results of the study show that promotional costs have a positive and significant effect on sales growth. These findings indicate that well-planned and structured promotions play an important role in contributing to the company’s revenue growth.